Tracing microbial carbon sources in hydrothermal sediments by 13C isotopic analysis of bacterial and archaeal ribosomal RNA - MacGregor, Barbara; Boschker, Henricus T. S.; Hoer, Daniel; Albert, Daniel B.; Mendlovitz, Howard; Teske, Andreas (Frontiers in Microbiology, 2025)
Microbial communities in hydrothermal sediments of Guaymas Basin assimilate a wide range of carbon sources, detrital organic matter, DIC of hydrothermal and water column origin, as well as methane, light alkanes and petroleum hydrocarbons. Here we analyze the abundances and 13C-isotopic values of these carbon pools, and assess the relative importance of these carbon sources by comparison with δ13C-isotopic composition of bacterial and archaeal rRNA. In almost all hydrothermal sediments, δ13C-rRNA values for bacterial and archaea are lighter (more 13C-depleted) than those of TOC and DIC, indicating that carbon from 13C-depleted methane permeates the microbial food web, with no systematic preference for bacteria or archaea. However, the omnipresence of detrital organic matter of photosynthetic origin means that any methane signal in bacterial and archaeal δ13C-rRNA values is diluted by the heterotrophic background. In non-hydrothermal background sediment where methane is lacking, the δ13C-rRNA values for bacterial and archaea are heavier (less 13C-depleted) and indicate the preferential utilization of detrital TOC of photosynthetic origin. The presence of petroleum in some methane-rich hydrothermal cores does not visibly change the δ13C-rRNA values for bacterial and archaea, since the δ13C-isotopic composition of hydrothermal petroleum in Guaymas Basin is similar to its source, detrital organic carbon, and thus does not separate fossil carbon utilizers from general heterotrophs. When δ13C-depleted methane competes with high concentrations of δ13C-repleted (heavier) short-chain alkanes, δ13C-rRNA values for bacteria and archaea are noticeably heavier than those in methane-rich but alkane-poor sediments, suggesting short-chain alkane incorporation. Under alkane-rich conditions, consistent differences between bacterial and archaea δ13C-rRNA were observed, suggesting the impact of distinct bacterial and archaeal alkane assimilation pathways. To summarize, we note that the availability of different sedimentary or hydrothermal carbon sources—in particular hydrothermal methane—is reflected in changing δ13C-rRNA values for bacteria and archaea.